Chlorinated Pesticide Residues in fruits and Vegetables - Chakrabarty, I.; Sharma, G.P.; Tyagi, B.P.; Dutt, Prashant (Asian Journal of Chemistry, 2010)
412 samples of different fruits and vegetables were collected from some districts of western Uttar Pradesh and Delhi (India) and analysed for organochlorine pesticides residues by GLC using electron capture detector. Residues of BHC (benzene hexachloride) and DDT (dichloro diphenyl trichloro ethane) were detected in 391 samples of vegetables and fruits. A total of 373 sample were lying below the tolerance limit while 18 sample shown comparatively higher value for BHC & DDT. For six samples these values found exceedingly high in comparision to tolerance limit of 0.15 and 1.25 ppm. as recommeneded by WHO/FAO.